Ghana country brief: Understanding the differences between child stunting and anemia reduction and identifying outstanding challenges - Aryeetey, Richmond; Atuobi-Yeboah, Afua; van den Bold, Mara; Nisbett, Nicholas (International Food Policy Research Institute, 2020)
In the past decade, Ghana has seen a significant reduction in stunting among children under five years of age. However, anemia only declined marginally over the same period, with the result that the rate of child anemia continues to be a severe public health emergency. These changes occurred within a socioeconomic context considered favorable for nutrition outcomes, marked by expansion and diversification of the economy, and investments in key infrastructure, healthcare, education, and water and sanitation. The Stories of Change in Nutrition study in Ghana aimed to better understand the changes in stunting and anemia between 2009 and 2018, as well as the potential drivers of these changes. Such findings can be used to inform agendasetting, implementation of existing policies, and future planning at national and subnational levels in Ghana. This study’s findings are important because both stunting and anemia are linked to significant adverse health and well-being impacts, particularly in low-income settings [1], and are listed among the global targets for nutrition for 2025 agreed by national ministers of health (including Ghana’s) at the World Health Assembly.